2021
DOI: 10.1021/acs.chemmater.1c02793
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Disordered Layered-Herringbone Phase in Organic Semiconductors Unveiled by Electron Crystallography

Abstract: The control of two-dimensional layered crystalline and/or liquid crystalline phases for π-extended organic molecules is crucial for expanding the potential of organic electronic materials and devices. In this work, we develop unique solution-processable organic semiconductors based on the unsymmetric substitution of [1]­benzothieno­[3,2-b]­[1]­benzothiophene (BTBT) with two different substituents, namely, phenylethynyl (PE) and normal alkyl with different chain lengths n (−C n H2n+1), both of which exhibit str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 90 publications
1
34
0
Order By: Relevance
“…This diagonal packing was in good correlation with the DFT calculated electrostatic potential maps, in which p - AID demonstrated a higher propensity to form edge-to-face packing, compared to o - AID . In addition, these diagonal peaks are consistent with other well-known small molecules, such as DNTT and tetrabenzoporphyrin, that exhibit offset packing, with respect to the substrate, which potentially leads to higher charge-transfer mobilities due to diminished grain-boundary effects in thin films. The significant differences observed here on o - AID and p - AID vs ID-C can be attributed to the thermally robust and coplanar conformation of o - AID and p - AID , which are promoted by intramolecular H-bonds. Because the H-bonds were not disrupted at higher temperatures, the rigid structures could be maintained to facilitate strong intermolecular interactions and firm molecular conformations for the formation of highly crystalline thin films with thermal annealing.…”
supporting
confidence: 81%
“…This diagonal packing was in good correlation with the DFT calculated electrostatic potential maps, in which p - AID demonstrated a higher propensity to form edge-to-face packing, compared to o - AID . In addition, these diagonal peaks are consistent with other well-known small molecules, such as DNTT and tetrabenzoporphyrin, that exhibit offset packing, with respect to the substrate, which potentially leads to higher charge-transfer mobilities due to diminished grain-boundary effects in thin films. The significant differences observed here on o - AID and p - AID vs ID-C can be attributed to the thermally robust and coplanar conformation of o - AID and p - AID , which are promoted by intramolecular H-bonds. Because the H-bonds were not disrupted at higher temperatures, the rigid structures could be maintained to facilitate strong intermolecular interactions and firm molecular conformations for the formation of highly crystalline thin films with thermal annealing.…”
supporting
confidence: 81%
“…In contrast, PE-BTBT-Cn with longer alkyl chains (n = 8, 10, 12) exhibits higher mobility of approximately 7 cm 2 V À1 s À1 than PE-BTBT-C6 by constructing bilayeredherringbone packing associated with the unsymmetrical length of the substituents. [54] Although defects such as grain boundaries that decrease electrical properties are inevitable during the film formation, postthermal annealing at crystalline-SmX transition temperature region allows the molecules to minimize defect formation and provides higher packing density with the reorganization of liquid crystals. Han et al reported that 2-(4-dodecyl thiophenyl) [1]dibenzothiopheno[6,5-b:6 0 ,5 0 -f]-thieno[3,2-b]thiophene (DBTTT-Th-C12) demonstrated molecular reorganization via thermal annealing.…”
Section: Field-effect Transistor Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 54 ] Copyright 2022, American Chemical Society. (f) Illustration of the homotropic alignment and (g) the corresponding atomic force microscopy (AFM) topographic profiles of DBTTT‐Th‐C12 after thermal annealing at the range of smectic phase transition temperature.…”
Section: Field‐effect Transistor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, disorder occurs when atoms, functional groups or even whole molecules are located in different positions in different unit cells in the crystal (Mu ¨ller et al, 2006). Usually, disorder occurs in only some parts of the molecule, such as freely rotating methyl (Kaiser Morris et al, 1997;Roessler et al, 2000) or tert-butyl groups, solvent molecules (Teeter, 1992), and other organic functional groups or long side chains (Inoue et al, 2022). Detecting and modelling disorder is important not only in crystallography (Dittrich, 2021), but also in other scientific fields, including materials chemistry (Varn & Crutchfield, 2015), the pharmaceutical industry (Dittrich, 2021) or the study of protein functions (Atkins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%